Effect of reaction temperature and flow rate of precursor on formation of multi - walled carbon nanoptubes - Tee, Jia Chee, author; Mohd. Abdul Aziz Saidin, author; Ahmad Fauzi Ismail, 1966-, author; International Conference on Nanoscience and Nanotechnology (2008: Selangor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL